Adequate housing for low-income families and its relationship to sustainable standards: A sociological study on a sample of beneficiaries in the Dubai city - aljaaidi, Maryam Saleem; Al-Hourani, Mohammed Abdel Karim (Al-Adab Journal, 2022)
This study assesses the level of satisfaction in housing for people with special needs in the Emirate of Dubai in terms of the availability of services and the standard of sustainability and social sustainability. To achieve the objectives of the study, a questionnaire was designed and applied to a random sample of 100 beneficiaries from the housing of the Mohammed bin Rashid Housing Establishment. Descriptive and analytical statistics (frequencies, percentages, arithmetic mean, standard deviation and multi regression coefficient) were used to find out the attractiveness of the demographics of the respondents, and to analyse the study data in an integrated set of factors associated with the standard and official code. The results of the statistical analysis revealed that there was no statistically significant relationship between the independent variables (owner’s gender, marital status, husband’s age, wife’s age, husband’s occupational status, wife’s occupational status, husband’s educational level, wife’s level, average monthly family income from all Resources, duration of residence) and a measure of proximity to service availability, environmental sustainability, and social sustainability on the other hand.